261 Effects of soy Protein Concentrate Replacing Animal Protein Supplements on Modulation of Mucosa-Associated Microbiota in Relation to Intestinal Health of Nursery Pigs. (21st September 2022) - Deng, Zixiao; Duarte, Marcos Elias E; Kim, Sung Woo
Abstract: This study aimed to investigate the effects of soy protein concentrate (SPC) replacing animal protein supplements on modulation of mucosa-associated microbiota in relation to intestinal health of nursery pigs. Weaned pigs (n = 56; 6.4 ± 0.6 kg BW) were allotted to 5 treatments in a randomized complete block design (RCBD) with initial BW and sex as blocks and fed for 35 d in 3 phases (P1/2/3 for 10/12/13 d, respectively). Dietary treatments were NC (n = 12): a diet with fish meal 4/2/1%, poultry meal 10/8/4%, and blood plasma 4/2/1% for P1/2/3, respectively; RFM (n = 12): NC with SPC replacing fish meal; RPM (n = 12): NC with SPC replacing poultry meal; RBP (n = 12): NC with SPC replacing blood plasma, and PC (n = 8): NC with SPC replacing all animal protein supplements. All diets were formulated to meet the nutrient requirements by NRC (2012). On d 35, pigs were euthanized to collect jejunal mucosa to evaluate intestinal health and microbiota. PC increased (P < 0.05) Lactobacillaceae (1.04 to 8.15%), and tended to increase (P = 0.073) Prevotellaceae (7.48 to 18.94%), whereas it decreased (P < 0.05) Chao1 index (81.3 to 15.8), Helicobacteraceae (27.95 to 3.02), and tended to reduce (P = 0.099) Campylobacteraceae (2.95 to 0.13). RPM tended to increase (P = 0.090) Prevotellaceae (7.48 to 17.16%) and reduced (P < 0.05) Helicobacteraceae (27.95 to 11.02%) without affecting Chao 1. Decreased Chao 1 was correlated to reduced feed intake and therefore, weight gain of pigs. In conclusion, the use of SPC replacing all animal proteins in nursery diets benefited the composition of the jejunal mucosa-associated microbiota, whereas feed intake and weight gain were reduced. The use of SPC replacing only poultry meal, however, benefitted the composition of the jejunal mucosa-associated microbiota without affecting feed intake and weight gain of nursery pigs.